Characteristics of medium-speed vertical axis wind turbine wind wheels - Rozhkova, L (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes)
The article deals with the state of autonomy of energy supply in the world, the state of this issue in Ukraine, the state of production of autonomous low-power wind turbines in the world and Ukraine. Autonomous low power wind turbines offer the use of new vertical type axial wind turbines with blades of the original shape, which have a sufficiently high wind energy utilization rate and may have less value compared to world models. They have self-starting wind wheels, can do even at low wind speeds and do not need to orient the wind wheels to the wind, like wind wheels with a horizontal axis. Particularly appropriate is the latter property in conditions where the wind direction changes constantly and unpredictably. The experimentally obtained characteristics of the power of vertical axial wind wheels of a new type are given. Methods for determining the performance of the wind farms offered are shown.